Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ani9070406
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals Up-Regulation of APR Signaling, LXR/RXR and FXR/RXR Activation Pathways in Holstein Dairy Cows Exposed to High-Altitude Hypoxia

Abstract: Changes in the environment such as high-altitude hypoxia (HAH) high-altitude hypoxia can lead to adaptive changes in the blood system of mammals. However, there is limited information about the adaptation of Holstein dairy cows introduced to high-altitude areas. This study used 12 multiparous Holstein dairy cows (600 ± 55 kg, average three years old) exposed to HAH conditions in Nyingchi of Tibet (altitude 3000 m) and HAH-free conditions in Shenyang (altitude 50 m). The miRNA microarray analysis and iTRAQ prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Unlike male, in female three top canonical pathways showed a differentially expressed pattern when compared between acute hypoxia and preconditioning groups with normoxia (AHF vs NF and PHF vs NF). In the present study, since LXR/RXR pathway showed an upregulation in AHF and down regulation in PHF and the activation of LXR/RXR leads to alleviate inflammation (Kong et al, 2019), it is legitimate to state that the neuroprotection in female might come faster by reducing inflammation in PHF eventually. Acetyl-CoA, as a central metabolic intermediate, is widely used in macromolecule biosynthesis and energy production to support cell growth and proliferation (Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…Unlike male, in female three top canonical pathways showed a differentially expressed pattern when compared between acute hypoxia and preconditioning groups with normoxia (AHF vs NF and PHF vs NF). In the present study, since LXR/RXR pathway showed an upregulation in AHF and down regulation in PHF and the activation of LXR/RXR leads to alleviate inflammation (Kong et al, 2019), it is legitimate to state that the neuroprotection in female might come faster by reducing inflammation in PHF eventually. Acetyl-CoA, as a central metabolic intermediate, is widely used in macromolecule biosynthesis and energy production to support cell growth and proliferation (Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…These events are consistent with chronic stress affecting the physical conditions and increasing the vulnerability of animals to infection and disease. Several studies have investigated the adaptation of cattle managed on pasture in high-altitude regions (86,87). Kong et al investigated the miRNA expression profiles of two breeds of cattle, and found that the levels of circulating miR-155 and miR-17-5p were upregulated in Jersey cows (86), whereas miR-let7a-5p, miR-19a, and miR-181a were upregulated in Holstein cows (87).…”
Section: Environmental Stressmentioning
confidence: 99%
“…In addition to its role as a kinase, FAK is involved in cell proliferation, adhesion, migration, invasion and apoptosis [79][80][81][82]; however, acute response signals, LXR/RXR activation, and FXR/RXR activation were significantly enriched after the tumor was observed. It has been reported that FXR/RXR activation may attempt to reduce inflammation, usually in conjunction with LXR and other receptors, to activate homeostasis in cholesterol and triglyceride metabolism and inhibit inflammation [83].…”
Section: B16 Melanoma-bearing Micementioning
confidence: 99%
“…Similarly, the pathway analysis showed that the pathways at different time points had their own characteristics, and some of them were reported to be associated with prostate cancer (Table 7). For example, before the tumor was palpable, FXR/RXR activation, LXR/RXR activation [83], mitochondrial dysfunction, acute phase response signaling and other pathways were significantly enriched. It has been reported that the activation of the LXR/RXR and FXR/RXR pathways may alleviate inflammation.…”
Section: Rm-1 Prostate Cancer-bearing Micementioning
confidence: 99%
See 1 more Smart Citation